“Picture Me Different”: Challenging Community Ideas about Women Released from Prison - Pickering, Barbara J. (Canadian Journal of Counselling and Psychotherapy, 2014)
This research into social justice explored how women transitioning from prison into the community can raise awareness and challenge stigmatic attributions that interfere with successful reintegration. Using the guiding principles of photovoice and action research, a group of 5 formerly incarcerated women created banners with the intention of dissemination leading to raised community awareness. Thematic analysis through the lenses of relational cultural theory, social capital, and feminist inquiry rendered overarching themes of helping my neighbour understand and my need for connection. Effects of the experience on participants, counselling implications, and how this research was put into action are discussed.